The Importance of G-protein Coupled Estrogen Receptor in Patients With Fibromyalgia - Tuba KOCA; Burhan KOÇYİĞİT and Muhammet SEYİTHANOĞLU and Ejder BERK (Archives of Rheumatology, 2019)
Objectives: This study aims to analyze the G-protein coupled estrogen receptor (GPER/GPR30) activity in patients with fibromyalgia syndrome (FMS). Patients and methods: We enrolled 40 female patients with FMS (mean age 42.9±11.2 years; range, 18 to 64 years) diagnosed according to the 2010 American College of Rheumatology classification criteria and 30 age- and body mass index-matched female healthy controls (mean age 43.7±13.6 years; range, 19 to 64 years). Sex hormones of patients (morning) including estradiol, follicle stimulating hormone, luteinizing hormone, and prolactin (PRL) were recorded. FMS severity was assessed by Fibromyalgia Impact Questionnaire (FIQ). Serum GPER levels were measured by using a quantitative sandwich enzyme-linked immunosorbent assay method with a commercial kit. Results: G-protein coupled estrogen receptor levels were 0.11 (0.02-0.9) ng/mL in the FMS patients and 0.059 (0.01-0.13) ng/mL in controls, with a statistically significant difference (p=0.037). GPER levels were positively correlated with age and negatively correlated with PRL, while they were not correlated with FIQ. Differential diagnosis for FMS with receiver operating characteristic (ROC) analysis for the serum GPER levels was statistically significant (area under the ROC curve: 0.653, confidence interval: 0.522-0.785, p=0.029). High values indicated FMS, with a threshold of >0.075, sensitivity of 60%, and specificity of 60%. Conclusion: The GPER levels of FMS patients were higher than those of the controls. Thus, GPER levels may be considered as a biomarker in the diagnosis of FMS independent of disease severity.